Physical activity during pregnancy in women with type 1 or type 2 diabetes: A scoping review - Holly Mei Jones; Lolwa Alyafei; Laura Macro; Gina Gardener; Emma Cockcroft; Rob Andrews; Richard M. Pulsford (Diabetic Medicine, 2026)
Abstract Aim Physical activity (PA) is recommended during pregnancy for its health benefits. While general PA guidance exists for uncomplicated pregnancies, evidence specific to women with pre‐existing type 1 diabetes or type 2 diabetes (T1D; T2D) is limited. This scoping review synthesised available evidence regarding PA during pregnancy among women with pre‐existing diabetes to identify evidence gaps and inform future research. Methods Systematic searches of MEDLINE, Embase, Web of Science, Scopus, CINAHL, and SportDiscus were conducted. Studies were eligible if they reported PA participation, evaluated PA interventions, or explored PA‐related experiences in pregnant women with T1D or T2D. Two reviewers independently screened titles, abstracts, and full texts. Data were extracted and synthesised narratively according to study design, PA measurement methods, and reported associations with diabetes or pregnancy outcomes. Results Twenty‐three studies were included. Overall, the literature reports that PA levels among women with pre‐existing diabetes are typically below recommended levels and decline across pregnancy. Qualitative studies identified barriers to PA, including physical discomfort, fear of glycaemic instability, and inadequate social support. Methodological limitations were common, including reliance on self‐reported PA, frequent aggregation of different diabetes types, a lack of longitudinal study designs, and scarce integration of objective PA measurement with glucose monitoring. Additionally, qualitative studies rarely focused on PA behaviours and experiences, and no studies explored the experiences of healthcare professionals supporting these women. Conclusion Evidence on PA during pregnancy in women with pre‐existing diabetes remains sparse and methodologically limited. Future research should prioritise longitudinal designs, objective PA measures alongside contemporaneous glucose monitoring, and incorporate qualitative research focused on barriers and facilitators to PA.